Enhanced Visible Transmittance of Thermochromic VO2 Thin Films by SiO2 Passivation Layer and Their Optical Characterization - Jung-Hoon Yu (Materials, 2016)
This paper presents the preparation of high-quality vanadium dioxide (VO2) thermochromic thin films with enhanced visible transmittance (Tvis) via radio frequency (RF) sputtering and plasma enhanced chemical vapor deposition (PECVD). VO2 thin films with high Tvis and excellent optical switching efficiency (Eos) were successfully prepared by employing SiO2 as a passivation layer. After SiO2 deposition, the roughness of the films was decreased 2-fold and a denser structure was formed. These morphological changes corresponded to the results of optical characterization including the haze, reflectance and absorption spectra. In spite of SiO2 coating, the phase transition temperature (Tc) of the prepared films was not affected. Compared with pristine VO2, the total layer thickness after SiO2 coating was 160 nm, which is an increase of 80 nm. Despite the thickness change, the VO2 thin films showed a higher Tvis value (λ 650 nm, 58%) compared with the pristine samples (λ 650 nm, 43%). This enhancement of Tvis while maintaining high Eos is meaningful for VO2-based smart window applications.